Effects of pressed beet pulp silage inclusion in maize-based rations on performance of high-yielding dairy cows and parameters of rumen fermentation - J. Boguhn; H. Kluth; M. Bulang; T. Engelhard; M. Rodehutscord (Animal, 2010)
Beet pulp contains high amounts of pectins that can reduce the risk of rumen disorders compared to using feedstuffs high in starch. The objective was to study the effects of inclusion of ensiled pressed beet pulp in total mixed rations (TMR) for high-yielding dairy cows. Two TMR containing no or about 20% (on dry matter (DM) basis) beet pulp silage were used. The beet pulp silage mainly replaced maize silage and corn cob silage. The TMR were intentionally equal in the concentrations of energy and utilisable crude protein (CP) at the duodenum. TMR were fed to 39 and 40 dairy cows, respectively, for 118 days. The average daily milk yield was about 43 kg/day. No significant differences in milk yield and milk fat or milk protein content were detected. DM intake of cows was significantly reduced by the inclusion of beet pulp silage (23.0 v. 24.5 kg/day). However, a digestibility study, separately conducted with sheep, showed a significantly higher organic matter digestibility and metabolisable energy concentration for the TMR that contained beet pulp silage. In vitro gas production kinetics indicated that the intensity of fermentation was lower in the TMR that contained beet pulp silage. In vitro production of short-chain fatty acids, studied using a Rusitec, did not differ between the TMR. However, the inclusion of beet pulp silage in the ration caused a significant reduction in the efficiency of microbial CP synthesis in vitro. The amino acid profile of microbial protein remained unchanged. It was concluded that beet pulp silage has specific effects on ruminal fermentation that may depress feed intake of cows but improve digestibility. An inclusion of beet pulp silage of up to 20% of DM in rations for high-yielding dairy cows is possible without significant effects on milk yield and milk protein or milk fat.